'Let's Teach as We Preach': The Design of a Professional Development Initiative to Support Teacher Educators' Responsiveness to Diversity - Benjamin Ponet; Wendelien Vantieghem; Hanne Tack; Ruben Vanderlinde (MDPI AG, 2023)
(1) Background: In preparing the next generation of teachers, teacher educators are key actors in fostering diversity-responsive education. However, evidence-informed professional development initiatives (PDIs) are needed to raise teacher educators' awareness and increase their diversity-responsive practices. This study provides insight into the design of a PDI that addresses this need. (2) Methods: After consulting the educational literature to define PDI objectives and general design principles, a participatory design process was initiated at two teacher education institutions to create a tailored PDI. Therefore, semi-structured interviews were conducted with a key policy-maker of each institution (n = 2) and with all participating teacher educators (n = 19). (3) Results: The participatory design process resulted in (1) the identification of both institutional contexts and participant groups' needs and (2) the subsequent design of a PDI to support teacher educators' diversity-responsive practices. Particularly, a three-phased PDI was designed, of which the overall and context-tailored design choices are discussed. (4) Conclusions: This contextualised PDI is a unique and concrete contribution to the teacher educator literature. Moreover, three new design principles are proposed for teacher educator PDIs in general. This article might inspire policy-makers and teacher educators to design their own PDIs to foster responsiveness to diversity.